Glycovariant-detecting proof-of-concept lectin-immunoassay development for pancreatic cancer diagnostics - Pennamo, Henrik (My University, 2021)
Pancreatic cancer (PaCa), a condition with a 9 % 5-year survival rate, is difficult to diagnose due to its unclear symptoms, but research has revealed changes in protein expression, extracellular vesicle formation and glycan structures of cancerous cells and proteins, that could be used for diagnosis. In this work, lectins and antibodies were used in a fluorescence immunoassay to detect glycan changes on MUC1, extracellular vesicles through tetraspanins, and integrins, to evaluate their functionality for clinical diagnosis. A library of antibodies and lectins was used to capture proteins, from which other proteins and aberrant glycan structures were detected. PaCa discrimination was evaluated first with cell line culture mediums, then with pooled serum of healthy, benign, and cancerous cohorts, and finally with individual serums from those cohorts. Most assay combinations showed no PaCa discrimination, but candidates including Ma552 with UEA for fucose detection from MUC1, and anti-integrin α3 with UEA for fucose detection from integrin α3 revealed moderate PaCa discrimination, with peak values from a cohort of 19 samples at 40 % sensitivity and 92 % specificity for Ma552, and 60 % and 100 % respectively for anti-integrin αV, providing a proof-of-concept for further research into PaCa diagnostics.